Effect of Trade Openness, Foreign Direct Investment, and Labor on GDP Per Capita of ASEAN Countries - Azzahra Mubyaring Putri Sayekti; Tiara Ayu Kusumaningtyas; Jordan Putra Cahyono (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
Trade openness has been widely studied for its impact on economic growth, yet its specific role in ASEAN countries, with diverse levels of integration and trade policies, remains underexplored. This study examines the effects of trade openness, foreign direct investment (FDI), and labor on GDP per capita in ASEAN countries using panel data from 2008 to 2022. Employing a fixed-effect regression model with Driscoll-Kraay standard errors, the findings reveal that trade openness has a significant yet negative impact on GDP per capita, while FDI and labor exhibit significant positive effects. This study recommends ASEAN countries to diversify exports, reduce dependency on foreign inputs, strengthen local industries, attract high-quality FDI, and improve labor capacity through education and vocational training. Strengthening intraregional trade cooperation is also crucial to reduce development disparities and promoting inclusive growth.